PS-BPB10-1: INVOLVEMENT OF RENAL TUBULAR NFAT5 IN THE REGULATION OF BLOOD PRESSURE AND BODY FLUID VOLUME. (January 2023) - Izumi, Yuichiro; Hiramatsu, Akiko; Eguchi, Koji; Matsuo, Naomi; Deng, Qinyuan; Inoue, Hideki; Nakayama, Yushi; Nonoguchi, Hiroshi; Aramburu, Jose; Rodriguez, Cristina Lopez; Kakizoe, Yutaka; Adachi, Masataka; et al.
Abstract : Objective: Nuclear factor of activated T-cells 5 (NFAT5) is an osmoresponsive transcription factor that activates osmoprotective genes to protect cells against hypertonicity. Renal tubular cell-specific NFAT5 knockout (KO) mice have been shown to exhibit polyuria, hypernatremia, low urinary sodium excretion, and increased expression of the epithelial sodium channel (ENaC) in the kidney. In the present study, regulation of blood pressure (BP) as well as that of body fluid volume were examined in the wild type (WT) mice and NFAT5 KO mice. Methods: The BP of KO mice and WT mice was measured using radiotelemetry method. The mice were fed with regular salt diet (RSD, 0.3% NaCl chow) or high salt diet (HSD, 8% NaCl chow) followed by the treatment with amiloride, an ENaC blocker. To assess body fluid volume, the plasma renin activity (PRA) and the plasma aldosterone concentration (PAC) were measured at the condition of RSD and HSD, together with plasma arginine vasopressin (AVP) and hematocrit (Ht) levels. Results: Compared to WT mice, the mean BP was significantly higher in KO mice both at the condition with RSD and that with HSD in dark period, but not in light period. Treatment with amiloride significantly decreased the mean BP in KO mice with HSD to the level of WT mice with HSD in dark period. PRA, PAC, and AVP levels were not significantly different between in WT and KO mice with RSD. HSD significantly decreased PRA and PAC and tended to increase the AVP level both in WT and KO mice. The Ht level was significantly lower in KO mice than in WT mice regardless of RSD or HSD (WT with RSD, 42.6 ± 0.5%; WT with HSD, 42.8 ± 0.6%; KO with RSD, 38.3 ± 0.4%; KO with HSD, 39.0 ± 0.4%, n = 4). Conclusions: The results suggest that the renal tubular cell-specific NFAT5 KO mice exhibit excess body fluid retention induced by sodium reabsorption through ENaC, leading to salt-sensitive hypertension. Such phenotypes seem to be independent of the systemic renin-angiotensin-aldosterone and AVP systems. Renal tubular NFAT5 could integrate urine concentration and sodium reabsorption in the kidney, thus preventing salt-dependent hypertension.